Fun learning activities about nutritious food as an effort to introduce stunting at SDN Ligarmanah - Shanti Anggraeni Rachman; Hasna Fatharani Qodriyyah (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
Stunting has become a particular focus of national health issues. Stunting is when a child is less tall than other children his age, which also affects brain development and metabolic disorders in children. Stunting is caused by a lack of nutritious food intake in children over a long period. This service activity tries to provide stunting education related to healthy food to students at SDN Ligarmanah with fun learning activities. SDN Ligarmanah is one of the schools that has not received sufficient education about stunting, so it is the right target for getting an education. The method used is the compression method, which actively involves students in the learning process, consisting of students from classes 3A, 3B, 4A, and 4B, who were taken using the cluster random sampling technique. This service provides understanding and knowledge to Ligarmanah Elementary School students regarding nutritious food to prevent increased stunting, and the students can display an understanding response to stunting material.   Abstrak Stunting telah menjadi sorotan khusus dalam isu kesehatan nasional. Stunting merupakan kondisi kurangnya tinggi badan seorang anak jika dibandingkan dengan anak seusianya yang juga berpengaruh terhadap perkembangan otak dan gangguan metabolisme anak. Stunting disebabkan oleh kurangnya asupan konsumsi makanan bergizi pada anak dalam jangka waktu yang lama. Kegiatan pengabdian ini mencoba untuk memberikan edukasi stunting terkait makanan bergizi kepada siswa-siswi di SDN Ligarmanah dengan kegiatan pembelajaran yang menyenangkan. SDN Ligarmanah merupakan salah satu sekolah yang belum mendapatkan edukasi yang cukup mengenai stunting sehingga menjadi sasaran yang tepat untuk mendapatkan edukasi. Metode yang digunakan adalah metode demonstrasi, dengan melibatkan siswa secara aktif dalam proses pembelajaran yang terdiri dari siswa-siswi dari kelas 3A, 3B, 4A, dan 4B yang diambil menggunakan teknik cluster random sampling. Pelaksanaan pengabdian ini memberikan pemahaman dan pengetahuan siswa-siswi SDN Ligarmanah terkait makanan bergizi pencegah stunting meningkat serta siswa-siswi mampu memperlihatkan respons pemahaman terhadap materi stunting. Kata Kunci: Kuliah kerja nyata; makanan bergizi; pembelajaran menyenangkan; stunting